Mitochondria and Coenzyme Q10 in the Pathogenesis of Preeclampsia - Teran, Enrique; Hernández, Isabel; Tana, Leandro; Teran, Santiago; Galaviz-Hernandez, Carlos; Sosa-Macías, Martha; Molina, Gustavo; Calle, Andrés (Frontiers in Physiology, 2018)
Hypertensive disorders during pregnancy constitute one of the main causes of maternal and perinatal morbidity and mortality all around the world, and particularly in developing countries like Ecuador. However, although its impact in public health the primary pathophysiological processes involved are not completely know. It has been proposed, among other theories, that an abnormal placentation might induce an endothelial dysfunction responsible for the final clinical manifestations. Mitochondria, particularly from trophoblastic cells, is responsible for energy production that is extremely important for normal placentation and its malfunction produces higher amount of free radicals. In both processes coenzyme Q10 plays a crucial role as electron transport, then its role in the genesis and prevention of preeclampsia has been of interest and addressed by several research groups including ours. The proper understanding of these mechanisms might allow designing new and feasible strategies to reduce preeclampsia, particularly in Latin-American countries.